Balanced Scorecard as a tool for research and development performance management – a case study in an agriculture company - Kubáňková, Marie; Hyršlová, Jaroslava; Nedělník, Jan (Oeconomica, 2018)
Purpose: The growing number of research oriented to research and development (R&D) performance reflects broad debates dedicated to R&D evaluation, measurement of its effectiveness related to competitiveness and also R&D added value and cost management. Therefore many authors call for research focused on the implementation of strategic management accounting tools, primarily the Balanced Scorecard (BSC) used as a R&D management tool in small and medium-sized enterprises (SMEs). The aim of this paper is to contribute to the empirical knowledge of implementation of strategic management accounting tools in R&D performance management, with a primary focus on the BSC implementation in SMEs. Design/methodology/approach: The purpose of this paper is to propose a procedure for R&D performance management tailored for SMEs based on BSC. This paper also intends to be an inspiration for further research in this area. As a case study method is recommend by the literature when a particular management tool is a desired output, the case study was provided in a case company. The investigation lasted nine weeks, three key steps can be recognized: (1) reference framework development; (2) strategic goals of the case company and the status quo of R&D management identification (3) development a BSC for the case company. Findings: The case study concludes the BSC proposal as a system of interrelated indicators and a procedure for R&D performance management. The indicators transform the strategic goals of the company into a set of corresponding R&D goals. Hereby this paper responds to the challenges endorsed by the literature, specifically the call to investigate the implementation of BSC in R&D performance management. Research/practical implications: Empirical research of the practical implementation of strategic management accounting tools is of a crucial importance of the further development of this scientific discipline. Innovation management measurement as well as R&D performance management are subjects of interest for a number of expert studies. The ambition of this paper is to provide a procedure for SMEs how to manage R&D by BSC, and also to bring an inspiration for further research in this field. Originality/value: The added value of this paper is extension of the existing knowledge concerning the BSC used in the management of R&D performance.
Balanced Scorecard jako nástroj řízení výkonnosti výzkumu a vývoje - případová studie v zemědělské společnosti
Keywords: research and development; Balanced Scorecard; strategic management accounting; výzkum a vývoj; Balanced Scorecard; strategické manažerské účetnictví